Evaluation of sex differences in the stopover behavior and postdeparture movements of wood-warblers. (5th December 2017) - Morbey, Yolanda E; Guglielmo, Christopher G; Taylor, Philip D; Maggini, Ivan; Deakin, Jessica; Mackenzie, Stuart A; Brown, J Morgan; Zhao, Lin
Abstract : Sex-specific behaviors underlying avian protandry, where males arrive at breeding areas earlier than females, are still poorly understood for most species. We tested for sex-specific stopover behavior of Neotropical-Nearctic wood-warblers (Parulidae) at a stopover site on Lake Erie, Ontario, using radio telemetry and analysis of blood plasma. The sex differences we found were subtle and related to diel activity, and so likely do not contribute to protandry in a consistent way. Abstract: Sex differences in the behaviors underlying avian protandry, where males arrive at breeding areas earlier than females, are still poorly understood for most species. We tested for sex differences in stopover behavior, refueling rates, and postdeparture movements during spring migration in 2 consecutive years in wood-warblers (Parulidae) at a coastal site on Lake Erie, Ontario, using automated radio telemetry (black-throated blue warblers Setophaga caerulescens and magnolia warblers Setophaga magnolia ) and analysis of plasma metabolites as indicators of refueling (magnolia warblers, American redstarts Setophaga ruticilla, and common yellowthroats Geothylpis trichas ). We found no differences between sexes in stopover duration or refueling index, although we did find subtle sex differences in the onset and end of diel activity. Males of both species began to forage earlier in the morning than females in 2015, and adult males of both species ended diel activity later in the evening than adult females in 2014 and 2015. More obvious were annual differences in stopover duration and the timing of diel activity, with shorter stopovers and an earlier onset of diel activity in the year with a warmer spring. We also did not find any evidence that sexes differed in their postdeparture ground speeds or migration routes. In wood-warblers, males and females can differ in some aspects of their stopover ecology, but these differences are likely context dependent and likely do not drive protandry in a consistent way.